Estudo da integridade da aresta de machos de corte de HSS durante a retificação em várias condições de corte - Vendrame, Saimon (2015)
Taps are cutting tools usually made of high speed steel follows several stages. One of their manufacturing stage is the grinding of threads surfaces. Into this context, a manufacturer detected some problems such as grinding burning and burr formation on the machined surface. The burning phenomenon is considered a thermal origin damage on the surface and subsurface, that causes reduction in tap s life. Also, burr formation can adverselly affect the integrity of the tap cutting edges. In this context, this work presents a study of the phenomena of burning and burr formation during grinding of HSS taps. Initially, the problems were identified in a real conditions during their fabrication in the industry. Secondly, laboratory trials were carried out in a specially designed HSS workpiece sample that can reproduce the geometry of the cutting taps threads. The input variables were grinding wheel speed, work speed, radial depth of cut, cutting direction and thread edge geometry. The output parameters investigated were: thickness of affected layer, microhardness and analysis of the sample edges. After this stage, machining trials were performed again in the industry using the same methodology employed during laboratory trials. The results showed similarity between laboratory and industry trials. In general, the thickness of affected layer of workpiece increased with work penetration but decreased with increase in work speed. The grinding wheel speed and cutting direction parameters did not show significant influence on the thickness of such layer. The order of importance of input machining parameters on the burr formation is as follows: thread edge geometry, cutting direction, work speed, wheel speed and radial depth of cut. The increase in work speed, in general, reduced the burr size, whereas the burr size increase with grinding speed. Also, no significant influence of work speed on burrs size was observed during grinding trials perfomed in the industry.